2013
DOI: 10.2134/agronj2013.0240
|View full text |Cite
|
Sign up to set email alerts
|

Camelina Yield and Quality Response to Combined Nitrogen and Sulfur

Abstract: Camelina [Camelina sativa L. Crantz], an oilseed crop in the Brassicaceae family, was field tested at multiple locations in the Maritime Provinces of eastern Canada in 2012 to evaluate the effects of N and S on seed yield, protein content, protein yield, oil content, and fatty acid profile. The experiment was designed as a randomized complete block factorial design with six N rates (20, 40, 80, 120, 160, and 200 kg ha -1 N), two S rates (0 and 25 kg ha -1 S) and two lines of camelina (CDI005 and CDI007). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
49
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 33 publications
22
49
2
Order By: Relevance
“…Seed yield was significantly higher with higher doses of nitrogen and the resulting difference as compared to the lower dose was 0.11 t•ha , which guarantees a high yield of seeds. The effect of higher doses of nitrogen on the growth of the yield was confirmed in previous studies by other authors (Jiang et al, 2013;Jiang et al, 2014;Sintim et al, 2015). For the optimal dose of nitrogen for false flax Jiang et al (2013) the camelina requires about 12 kg of kg•ha -1 per 100 kg of expected seed yield.…”
Section: Yield and Yield Componentssupporting
confidence: 72%
See 3 more Smart Citations
“…Seed yield was significantly higher with higher doses of nitrogen and the resulting difference as compared to the lower dose was 0.11 t•ha , which guarantees a high yield of seeds. The effect of higher doses of nitrogen on the growth of the yield was confirmed in previous studies by other authors (Jiang et al, 2013;Jiang et al, 2014;Sintim et al, 2015). For the optimal dose of nitrogen for false flax Jiang et al (2013) the camelina requires about 12 kg of kg•ha -1 per 100 kg of expected seed yield.…”
Section: Yield and Yield Componentssupporting
confidence: 72%
“…The effect of higher doses of nitrogen on the growth of the yield was confirmed in previous studies by other authors (Jiang et al, 2013;Jiang et al, 2014;Sintim et al, 2015). For the optimal dose of nitrogen for false flax Jiang et al (2013) the camelina requires about 12 kg of kg•ha -1 per 100 kg of expected seed yield. Toncea (2014) reported that yield of camelina also depends on weather conditions and varieties.…”
Section: Yield and Yield Componentssupporting
confidence: 72%
See 2 more Smart Citations
“…For example, the maximum seed yield of camelina was attained with the application of 185-300 kg ha −1 N in Chile (Solis et al 2013). The optimum N rate for the highest yield ranged from 120 to 160 kg ha −1 N in eastern Canada (Jiang et al 2013). The maximum seed yield was achieved at a rate of 170 kg ha −1 N on the Canadian prairies (Malhi et al 2014).…”
Section: Introductionmentioning
confidence: 99%